MENGEMBANGKAN KEMAMPUAN MOTORIK KASAR MENGGUNAKAN MODEL DEMONSTRATION, METODE DRILL, DAN PERMAINAN TRADISIONAL EGRANG BATOK KELAPA - Hapipah, Hapipah; Maimunah, Maimunah (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2025)
This research is motivated by the low activity and development of children's gross motor skills, especially in performing coordinated movements. The purpose of this study is to describe teacher activities, analyze children's activities, and the results of gross motor development. This research method uses a qualitative approach with the type of Classroom Action Research (CAR) which is carried out in 4 meetings, the research setting is in group B1 children of TK Islam Khadijah Plus Banjarmasin totaling 20 children. The data collection technique uses observation and descriptive data analysis using tables and graphs. The results of the study show that (1) teacher activity at meeting 1 gets the category